USE OF CAD FOR APPAREL DESIGNING USING DECORATIVE MOTIFS OF JAMA MASJID - Nandini; Sakshi (International Journal of Research -GRANTHAALAYAH, 2018)
Indian has a rich collection of monuments belonging to different periods of history, with motifs of respective periods. These structures are being damaged due to various reasons, in order to preserve the decorative motifs of monuments the present study was planned with an objective to collect the motifs of Jama Masjid, Fatehpur Sikri and apply them on kurti to preserve the motifs and to diversify the product as consumers are demanding for new designs in apparels. The motifs were collected from the site and were used for apparel designing using Corel Draw software. Collected motifs were classified into broad and narrow border design, central design, and buti designs. These were used for designing on kurti using Computer aided designing. The designed products were evaluated by a panel of judges. The judges appreciated the motifs selected for designing and also had an opinion that if such products are available in the market, they will purchase them. The judges also suggested that such products can also be sold at the historical places as tourist visit and can purchase them as the souvenir of that place.